Nanofabrication by electron beam lithography and its applications: A review - Chen, Yifang (Microelectronic engineering, 2015)
[Display omitted] •This review focus on EBL on single/multilayer resists for pattern transfer.•Applications in nanoelectronic devices, nanophotonic structures and nanostructures.•10 EBL resists are reviewed, including PMMA, UVIII, ZEP, UVN-30, HSQ, SU-8, etc.•Focused e-beam was also applied for the surface modification of materials. This review covers a wide range of nanofabrication techniques developed for nanoelectronic devices, nanophotonic metamaterials and other nanostructures, based on electron beam lithography (EBL). Differing from earlier publications, this review particularly focuses on how to apply the property of EBL resists for constructing multilayer stacks towards pattern transfer. Most frequently used resists and their lithography property are first introduced, followed by categorizing multiple layers of resists for fulfilling various tasks in nanofabrication. Particularly, T shape gates for high electron mobility transistors (HEMTs), metallic tunneling junctions (MTJs) in single electron tunneling transistors (SETs), chiral structures and photonic crystals for optical metamaterials, templates for NIL and etching masks for nanoscale reactive ion etch (RIE) are reviewed. In the description of process development, scientific advances behind these fabricated nanostructures are described at the same time. By this way, this review aims to indicate that the development of nanofabrication techniques is essential for the rapid advances of nanoscience as a whole.